Association of General Obesity and Abdominal Obesity with the Prevalence of Urinary Incontinence in Women: Cross-sectional Secondary Data Analysis - Sunah PARK; Kyoung Ah BAEK (Tehran University of Medical Sciences, 2018)
Background: Urinary incontinence is prevalent among older adults worldwide and associated with lower quality of life. Obesity is highly associated with development or exacerbation of urinary incontinence. We examined the impact of different types of obesity (general obesity and abdominal obesity) on urinary incontinence. Methods: We employed 2007-2009 Korean National Health and Nutrition Examination Survey (KNHANES) with 4648 females over 19 yr of age. Body mass index, waist circumstance, total body fat percentage, trunk fat percentage, demographic variables, and potential confounding factors were assessed. Chi-square tests and logistic regression analysis were used.  Results: There were significant trends of increasing risk of urinary incontinence with increasing body mass index (P =.002), waist circumstance (P = .001), percent total body fat (P =.029) and percent trunk fat (P =.005). Regarding the association of urinary incontinence prevalence with different types of obesity, nonobese women with abdominal obesity had the highest odds ratio of urinary incontinence, followed by obese women with abdominal obesity (odds ratio = 1.59 and 1.55, respectively). Conclusion: Abdominal obesity may be more likely to be associated with urinary incontinence compared to overall obesity. Early screening and identification of abdominal obesity may be needed for older women to prevent or reduce urinary incontinence episodes.